Natural frequencies of twisted cantilever beam. (August 2019) - Malta, J; Jefri,; Bur, M; Satria, E
Abstract: This research is conducted to determine the natural frequencies of a twisted beam with different orientation of principal axes numerically using Autodesk Inventor. Further, the results are compared experimentally. To simplify in the analysis, the twisted cantilever beam is divided into two segments model. The orientation between two segments is simulated and tested variously. The natural frequencies obtained numerically and experimentally are selected only in transverse vibration based on the simulation of each mode shape of the cantilevered beam. In general, the natural frequencies of the simulated cantilever beam and experiment results tend to similar results.